Administrative empowerment of school principals and its relationship to organizational trust from the viewpoint of teachers in Karak Governorate - Rawashdeh, Sahar Rashid; Al-Taani, Hassan Ahmed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the level of administrative empowerment of school principals and its relationship to organizational trust from the viewpoint of teachers in Karak Governorate. To achieve the study objectives, a questionnaire was developed for the purpose of collecting data, and its validity and reliability were confirmed. The study reached the most important results: the respondents ’perceptions of the administrative empowerment variable with its dimensions were medium, and the respondents’ perceptions Towards the variable of organizational confidence in its dimensions came in a medium degree, as the results of the study showed that there is a correlative relationship with statistical significance at the level of significance (α≤0.05) between administrative empowerment in all its dimensions and organizational culture in all its dimensions, the results also indicated that there were no statistically significant differences at the level of significance (α≤0.05) in school teachers ’estimates of the level of organizational confidence and the level of administrative empowerment attributed to variables (gender, educational qualification, experience). In light of the results obtained, the researcher recommends; enhancing the level of administrative empowerment among school teachers by giving them administrative powers and allowing them to participate in making decisions, and improving the level of organizational confidence of school teachers by providing them with various opportunities for learning, training and development.